2018
DOI: 10.1002/advs.201801406
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Favorable Cation Antisite by Doping Halogen in Ni‐Rich Layered Cathode with Ultrahigh Stability

Abstract: The cation antisite is the most recognizable intrinsic defect type in nickel‐rich layered and olivine‐type cathode materials for lithium‐ion batteries, and important for electrochemical/thermal performance. While how to generate the favorable antisite has not been put forward, herein, by combining first‐principles calculation with neutron powder diffraction (NPD) study, a defect inducing the favorable antisite mechanism is proposed to improve cathode stability, that is, halogen substitution facilitates the nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…[110] More recently, Li et al reported that doping halogen in Ni-rich cathodes could induce favorable cation antisite formation, and hence significantly improve the electrochemical and thermal stability. [111] First-principles calculation revealed that the halogen substitution could facilitate the exchange of the adjacent Li + and Ni 2+ to from a lower total energy and more stable local octahedron structure, which is due to the stronger bond strength of X-Li than X-Ni. As shown in Figure 24a, the Figure 23.…”
Section: Anionic Dopingmentioning
confidence: 99%
See 4 more Smart Citations
“…[110] More recently, Li et al reported that doping halogen in Ni-rich cathodes could induce favorable cation antisite formation, and hence significantly improve the electrochemical and thermal stability. [111] First-principles calculation revealed that the halogen substitution could facilitate the exchange of the adjacent Li + and Ni 2+ to from a lower total energy and more stable local octahedron structure, which is due to the stronger bond strength of X-Li than X-Ni. As shown in Figure 24a, the Figure 23.…”
Section: Anionic Dopingmentioning
confidence: 99%
“…a) The effect of F, Cl, Br, and I substitution on the calculated antisite defect formation energies, the inset models are LOSH. [111] b) Schematic illustration of the preparation process of AS-LNCM, indicating that the LiF compounds migrate into the particles of Ni 0.85 Co 0.075 Mn 0.075 (OH) 3 and react with each other to facilitate O substituted by F; further sintering with LiOH generates the favorable antisite in the most stable LOSH to stabilize layered LNCM. [111] c) Room-temperature cycling performance over 200 cycles at a rate of 1C.…”
Section: Doping/coatingmentioning
confidence: 99%
See 3 more Smart Citations